Identification of Neisseria gonorrhoeae in Commercial Sex Worker Clients with and without Condom Use - Maulandi, Andi; Silviani, Yusianti (Jurnal Biologi Tropis, 2025)
This study investigates the prevalence of Neisseria gonorrhoeae among commercial sex workers and their clients in Pulau Baai, Bengkulu, with a focus on comparing infection rates between individuals who use condoms and those who do not. The primary objective is to assess the impact of condom usage on the prevalence of gonorrhea in this high-risk population. A cross-sectional observational design was employed, involving 40 male participants who had engaged with commercial sex workers in the Pulau Baai area. The participants were divided into two groups based on their condom use. Urethral secretion samples were collected and analyzed via Gram staining for Neisseria gonorrhoeae detection. The study found no cases of Neisseria gonorrhoeae in any of the samples, with all 36 condom users and 4 non-users testing negative. These results suggest no gonorrhea infections in the studied population, regardless of condom use. However, due to the limitations of the Gram staining method, further research using more sensitive diagnostic techniques and a larger sample size is recommended to verify these findings.